A New Concept for Cervical Expansion Screws Using Shape Memory Alloy: A Feasibility Study - Grunert, Ronny; Winkler, Dirk; Knoop, Nikolas; Weidling, Martin; Matzke, Cornelia; Scholz, Sebastian; Meixensberger, Juergen; Arlt, Felix (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background In general, sufficient anchoring of screws in the bone material ensures the intended primary stability.Methods Shape memory materials offer the option of using temperature-associated deformation energy in a targeted manner to compensate the special situation of osteoporotic bones or the potential lack of anchoring. An expansion screw was developed for these purposes. Using finite element analysis (FEA), the variability of screw configuration and actuator was assessed from shape memory. In particular, the dimensioning of the screw slot, the actuator length, and the actuator diameter as well as the angle of attack in relation to the intended force development were considered.Results As a result of the FEA, a special configuration of expansion screw and shape memory element could be found. Accordingly, with an optimal screw diameter of 4 mm, an actuator diameter of 0.8 mm, a screw slot of 7.8 mm in length, and an angle of attack of 25 degrees, the best compromise between individual components and high efficiency in favor of maximum strength can be predicted.Conclusion Shape memory material offers the possibility of using completely new forms of power development. By skillfully modifying the mechanical and shape memory elements, their interaction results in a calculated development of force in favor of a high primary stability of the screw material used. Activation by means of body temperature is a very elegant way of initializing the intended locking and screw strength.
Keywords: screw implant; shape memory alloy; finite element analysis